The C-terminal region of Reelin is necessary for proper positioning of a subset of Purkinje cells in the postnatal cerebellum. (12th November 2016) - Nakamura, Kota; Beppu, Mako; Sakai, Kaori; Yagyu, Hayata; Matsumaru, Saori; Kohno, Takao; Hattori, Mitsuharu
Highlights: Tens of Purkinje cells are located ectopically in mice that lack the Reelin C-terminal region. Ectopic PCs are selectively found in the lobule VI/VII and often form clusters. Insufficient cell-autonomous Reelin signaling is likely to cause the ectopicity. Reelin protein with intact CTR binds preferentially to Purkinje cells. Abstract: In the normal cerebellum, Purkinje cells (PCs) are generated in a zone along the ventricular surface, migrate radially, and align to form a single-cell layer. However, in mice lacking the secreted protein Reelin or its downstream adaptor protein Dab1, the majority of PCs are located ectopically in the deep cerebellar mass. Nonetheless, how Reelin regulates migration and alignment of PCs remains incompletely understood. Reelin has a highly-conserved C-terminal region (CTR), which is required for its full activity. Here, we report an abnormality of the cerebellum in Reelin CTR-lacking knock-in (ΔC-KI) mice. In the ΔC-KI mice, cerebellar formation was largely normal, but some PCs in selected regions were found to be located ectopically and to frequently form clusters. Ectopic PCs contained a higher amount of Dab1 protein and functional Reelin receptors, including mainly very low-density lipoprotein receptor than correctly-aligned PCs. Decreasing Dab1 gene dosage exacerbated mislocalization of PCs and the cerebellar structure in Reelin ΔC-KI mice. These results indicate that ectopic PCs in ΔC-KI mice failed to receive sufficient Reelin signaling en route to their final destinations. Further, we also found that Reelin protein with intact CTR binds preferentially to PCs. Thus, it was suggested that the extent or quality of Reelin/Dab1 signaling that PCs require for correct positioning vary and that Reelin with intact CTR is required for that of a certain subset of PCs.